The Spatial Effect of Agricultural Sector Growth in West Java: A Spatial Approach to Panel Data - Adi Hadianto; Harianto Harianto; Bonar Marulitua Sinaga; Bagus Sartono (Institut Pertanian Bogor, 2022)
The agricultural sector is strategic and the third-largest contributor to the GRDP of West Java Province, but its growth has slowed during the 2016–2019 period. The slow growth rate can be caused by the determinants of the growth of the agricultural sector itself and is very likely to be affected by the spatial interaction between regions in the province. Therefore, this study aims to analyze the spatial effect between regions on the growth of the agricultural sector in West Java and identify the factors that influence the growth of the agricultural sector within the province by using spatial analysis of panel data. The results reveal that the appropriate model is a fixed effect spatial error model, which shows an effect of spatial interaction between regions on the growth of the agricultural sector in West Java Province. The factors that affect the growth of the agricultural sector are agricultural credit, agricultural road infrastructure, and diversification of economic activities. Keywords: agricultural sector growth, spatial autoregressive, spatial error model, spatial panel data